Cryptosporidiosis causing severe persistent diarrhea in a patient with multiple myeloma: A Case report and brief review of literature - Nidhi Tandon; Sudeep Gupta (Indian Journal of Medical and Paediatric Oncology)
Cryptosporidiosis is a protozoal infection that leads to self-limited diarrheal disease in immunocompetent individuals and a more severe illness in immunocompromised patients especially those infected with the human immunodeficiency virus. Although patients with hematolymphoid malignancies can develop this infection, it is an uncommon cause of diarrhea in these patients. The patient was a 64-year-old woman, a known case of multiple myeloma for 17 years, who had been treated with multiple lines of chemotherapy earlier. She was being treated with lenalidomide plus dexamethasone for active myeloma at the time of this episode. She presented with profuse watery diarrhea of 15 days duration that was proven to be due to Cryptosporidium parvum on stool examination. The diarrheal illness resolved after treatment with nitazoxanide. Although uncommon, cryptosporidial infection should be suspected in patients with hematological malignancies who have persistent diarrhea. Stool examination with the modified acid-fast Kenyoun stain establishes the diagnosis in the majority of cases. Antiparasitic treatment is effective in controlling the infection.